Assessment of different treatment methods by microbial-induced calcite precipitation for clayey soil improvement - Cheng, Liang; Shahin, Mohamed (Canadian Geotechnical Society, 2015)
Microbial-induced calcite precipitation (MICP) utilises the metabolic pathway of ureolytic bacteria to form calcium carbonate precipitation throughout the soil matrix, leading to increased soil strength and stiffness. MICP has proved to be an efficient technique for treatment of clean sand; however, there is lack of knowledge for MICP treatment of clayey soils. This paper assesses three different MICP methods including injection, premixing and diffusion, for treatment of clayey sand containing up to 20% clay content. The results indicate that the injection method is applicable only of treating sand columns that contain < 5% clay content, with an exponential relationship between the unconfined compressive strength (UCS) and calcite content similar to that of treated pure sand samples. The premixing method, on the other hand, allowed a homogeneous placement of the bacteria cells in the sand columns and the subsequent injection of cementation solution under low pressure of 100 kPa enabled an adequate bio-cementation along specimens that contain up to 10% clay content, resulting in up to 150% increase in the UCS values. The results also show that sand columns with 20% clay content can be treated using the diffusion method, leading to increased UCS values of up to 200% depending on the treatment duration. The overall conclusion of this study is that bio-cementation of clayey soils is a tremendous challenge and requires further investigation on the ureolytic bacteria placement and supply of cementation solution at large scale before field application.